Sleep Quality, School Environment, and Quality of Life among High School Students: A Comparative Study: A Comparative Study - Bawiling, Nancy Sylvia; Supit, Alva Sahiri Alexander (Journal of Educational, Health and Community Psychology, 2025)
Adolescence is a critical developmental period in which sleep quality and the school environment shape health and well-being. We examined differences in sleep quality and quality of life (QoL) between Indonesian students attending a public (n=500) versus a Christian (n=50) high school and explored sex-specific patterns. In this cross-sectional study (May–June 2024), we administered the Pittsburgh Sleep Quality Index (PSQI) and the WHOQOL-BREF (physical, psychological, social, environmental domains). Females reported poorer sleep than males (PSQI: 6.40 ± 3.04 vs 5.51 ± 3.01; p=0.001), and lower general QoL (7.09 ± 1.44 vs 7.54 ± 1.53; p<0.001). Christian-school students scored higher on psychological QoL (Domain 2: 21.26 ± 3.43 vs 20.08 ± 3.55; p=0.024) and general QoL (7.78 ± 1.51 vs 7.20 ± 1.48; p=0.013) compared with public-school peers; sleep quality did not differ (p=0.733). Across all students, poorer sleep correlated with worse physical health (Domain 1: r = -0.15, p<0.001) and lower general QoL (r = -0.09, p=0.033); the sleep–physical QoL association persisted in males (r = -0.23, p=0.001) but not females. This study highlights the role of gender and school environment in understanding sleep quality and quality of life in adolescents. Practically, results support school-based sleep health education and leveraging faith-based community assets to enhance psychological well-being in resource-constrained settings.